Digital Leadership in Action: A Case Study of Principal’s Technology-Based Supervision and its Impact on Teacher Development - Siswanto Siswanto; Bukman Lian; Muhammad Juliansyah Putra (Journal of Social Work and Science Education, 2026)
This qualitative case study investigated the role of a primary school principal in implementing technology-based academic supervision and teacher competency development. Data were collected through interviews, observations, and documentation at SDN 1 Sumber Hidup, Indonesia. Findings reveal three key strategies: needs-based training, the establishment of a teacher learning community (Kombel), and technology-based individual mentoring. The study demonstrates that a shift from a control-oriented to a coaching-oriented supervision model, facilitated by digital tools, fostered a collaborative professional culture and enhanced teacher capacity. The findings contribute to understanding how principals can operationalize instructional leadership in the digital era to build sustainable teacher professional development.